Identification of Human Fumarylacetoacetate Hydrolase Domain-containing Protein 1 (FAHD1) as a Novel Mitochondrial Acylpyruvase - Pircher, Haymo (American Society for Biochemistry and Molecular Biology, 2011)
The human fumarylacetoacetate hydrolase (FAH) domain-containing protein 1 (FAHD1) is part of the FAH protein superfamily, but its enzymatic function is unknown. In the quest for a putative enzymatic function of FAHD1, we found that FAHD1 exhibits acylpyruvase activity, demonstrated by the hydrolysis of acetylpyruvate and fumarylpyruvate in vitro, whereas several structurally related compounds were not hydrolyzed as efficiently. Conserved amino acids Asp-102 and Arg-106 of FAHD1 were found important for its catalytic activity, and Mg(2+) was required for maximal enzyme activity. FAHD1 was found expressed in all tested murine tissues, with highest expression in liver and kidney. FAHD1 was also found in several human cell lines, where it localized to mitochondria. In summary, the current work identified mammalian FAHD1 as a novel mitochondrial enzyme with acylpyruvate hydrolase activity.